Linking schools, universities, and businesses to mobilize resources and support for career choice and development of students who are visually impaired. (September 2016) - Patterson, John A; Loomis, Colleen
This study documents how linking schools, universities, and local organizations can make school curriculum more relevant for career development for students who are visually impaired. Two schools, one for the visually impaired with students aged 4–19 years and another school for students aged 11–19 years who have severe or profound learning difficulties, were part of the collaboration, along with local university students who were teachers in training. Outcomes included new curriculum material for use in public schools to sensitize sighted students on visual impairment. The project also initiated employment apprenticeships for two students who are visually impaired. Our findings suggest that we can educate multiple groups of students simultaneously while building stronger ties between schools, universities, and local public and private employers. Using an outreach approach results in building relationships that facilitate education and employment for students who are visually impaired. St. Vincent's School obtained consent for all participants in this study and participants chose to be identified, rather than have a pseudonym used.